Gamification in mobile shopping applications: A review in terms of technology acceptance model - Bayir, Talha; Akel, Gokhan (Springer, 2023)
Businesses add gamification to their mobile shopping applications to increase customer interaction and their continuance intention. It has been observed that, with gamification based mobile shopping activities, consumers have positive experiences, and their customer loyalty has increased. Therefore, it is crucial to research the effects of gamification content used in mobile shopping applications on consumers' tendencies to use or not use technology. This research aims to determine the effect of gamification activities offered in mobile shopping applications on users' perceived ease of use, perceived usefulness, attitude, and intention using the Technology Acceptance Model (TAM). The research used a convenience sample of 442 mobile shopping applications users living in Turkey and an online survey method was used to collect the research data. Considering the analyses of the research, the relationship levels between the variables were determined. There are significant relationships between PEOU and GAM (r = .939), PU and PEOU (r = .874), ATT and PU (r = .827), INT and ATT (r = .969). Reliability and validity analyses were applied. The factor loadings of the scales, and AVE value above .50, Cronbach's Alpha (C alpha), and CR value above .70 were considered statistically reliable and valid. The technique of structural equation modeling (SEM) was used to estimate the variables' effect and mediation levels. Then, it was found that perceived ease of use had a positive and significant mediating effect (beta = .339) between gamification and attitude variables. Similarly, perceived usefulness had a positive and significant (beta = .827) mediating effect between gamification and attitude variables.
Keywords: Gamification; Mobile shopping applications; Technology acceptance model